Simiao Decoction Alleviates Gouty Arthritis by Modulating Proinflammatory Cytokines and the Gut Ecosystem - Lin, Xiaoying; Shao, Tiejuan; Huang, Lin; Wen, Xianghui; Wang, Mingzhu; Wen, Chengping; He, Zhixing (Frontiers in Pharmacology, 2020)
Simiao decoction, a classical traditional Chinese medicine (TCM) formula, has been widely used for thousands of years due to its safety and efficiency in treating gouty arthritis. Utilizing serum proinflammatory cytokines and gut ecosystems, this study elucidated the mechanisms of alleviating gouty arthritis by Simiao decoction. Simiao decoction (4, 8 and 16 g/kg) was orally administered to gouty arthritis mice and febuxostat was given as a positive control. The spleen, kidney and liver indexes indicated that Simiao decoction was safe for the treatment of gouty arthritis in C57BL/6 mice. Besides, our study demonstrated that Simiao decoction was effective for reducing the level of serum uric acid and decreasing MPO, XOD and ADA activity, as well as alleviating gouty-related symptoms, such as foot swelling and pain. Moreover, Simiao decoction could also reduce some specific serum proinflammatory cytokines including IL-1, IL-9, IFN-, MIP-1 and MIP-1 We then surveyed the effects of Simiao decoction on the gut ecosystems in a systematic manner by combining network pharmacology, ELISA, western blot and illumina sequencing. In the murine of model of gouty arthritis, Simiao decoction could suppress NLRP3 inflammasomes expression, reduce gut apoptosis through modulating TNF-, Caspase 8 and AIFM1 protein expressions, affect lipid metabolism by regulating APOB, LPL, PPAR protein expressions and restore gut microbiota via reducing potential pathogens. Overall, these findings suggested that Simiao decoction was an effective therapeutic drug for gouty arthritis and the gut ecosystem might act as a potential anti-inflammatory target of Simiao decoction.